2014
DOI: 10.1371/journal.pone.0087568
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Immunosuppressive Treatment to Hemoperfusion Is Associated with Improved Survival after Paraquat Poisoning: A Nationwide Study

Abstract: Paraquat poisoning associates very high mortality rate. Early treatment with hemoperfusion is strongly suggested by animal and human studies. Although the survival benefit of additional immunosuppressive treatment (IST) in combination with hemoperfusion is also reported since 1971, the large-scale randomized control trials to confirm the effects of IST is difficult to be executed. Therefore, we designed this nationwide large-scale population-based retrospective cohort study to investigate the outcome of paraqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
61
1
8

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 34 publications
1
61
1
8
Order By: Relevance
“…On the other hand, MP, a kind of synthetic corticosteroid drug, can improve the survival rate of PQ patients mainly because of its potent antiinflammatory effects (Chen G.H. et al, 2002;Wu et al, 2014). In our study, MP treatment did not alleviate pulmonary fibrosis.…”
Section: Discussioncontrasting
confidence: 55%
“…On the other hand, MP, a kind of synthetic corticosteroid drug, can improve the survival rate of PQ patients mainly because of its potent antiinflammatory effects (Chen G.H. et al, 2002;Wu et al, 2014). In our study, MP treatment did not alleviate pulmonary fibrosis.…”
Section: Discussioncontrasting
confidence: 55%
“…Paraquat intoxication has been found to cause kidney damage in humans (Kim et al, 2009; Reigart et al, 1999; Wu et al, 2014); however, little is known about the effects of chronic low-level exposure to this chemical. In our previous study, we observed a significant positive trend in the rate of ESRD associated with increasing lifetime use of paraquat among pesticide applicators (Lebov et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, ingestion of the concentrated formulation is very toxic to humans, and it has been rigorously restricted or banned in many countries . Clinical management involves supportive care, as well as correction of acid base and electrolyte disturbances, and there is no specific antidotal treatment . Some studies mentioned that early haemoperfusion may improve patients' chances of survival in severe cases of acute paraquat poisoning …”
Section: Introductionmentioning
confidence: 99%
“…Clinical management involves supportive care, as well as correction of acid base and electrolyte disturbances, and there is no specific antidotal treatment . Some studies mentioned that early haemoperfusion may improve patients' chances of survival in severe cases of acute paraquat poisoning …”
Section: Introductionmentioning
confidence: 99%